2019
DOI: 10.4136/ambi-agua.2249
|View full text |Cite
|
Sign up to set email alerts
|

Validation of rainfall data estimated by GPM satellite on Southern Amazon region

Abstract: Rainfall is a meteorological variable of great importance for hydric balance and for weather studies. Rainfall estimation, carried out by satellites, has increased the climatological dataset related to precipitation. However, the accuracy of these data is questionable. This paper aimed to validate the estimates done by the Global Precipitation Measurement (GPM) satellite for the mesoregion of Southern Amazonas State, Brazil. The surface data were collected by the National Water Agency – ANA and National Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The availability of the TRMM data only to the end of December 2019; thus, the continued data was using the Global Precipitation Measurement (GPM) satellite product. The study of [26] was shown the correlation of GPM data above 0.83; therefore, it possible to use in this work.…”
Section: Rainfall Datamentioning
confidence: 96%
“…The availability of the TRMM data only to the end of December 2019; thus, the continued data was using the Global Precipitation Measurement (GPM) satellite product. The study of [26] was shown the correlation of GPM data above 0.83; therefore, it possible to use in this work.…”
Section: Rainfall Datamentioning
confidence: 96%
“…In contrast, the spatial differences between precipitation estimates by remote sensing and reanalysis, and the measurements at the weather stations can be partly due to differences in the spatial scales represented by these techniques. A rain gauge consists of a point measurement, while the gridded products (i.e., satellites and land surface models or reanalysis) obtain an average value over the analyzed pixel, although there are different adjustments depending on the local characteristics of each region [33,34]. As a result, satellites and reanalysis products have the ability to estimate precipitation events in areas that a rain gauge was unable to record [30].…”
Section: Spatial Variabilitymentioning
confidence: 99%
“…As a result, satellites and reanalysis products have the ability to estimate precipitation events in areas that a rain gauge was unable to record [30]. It should be noted that remote sensing products can mistakenly estimate precipitation events due to the thickness and temperature of clouds [34].…”
Section: Spatial Variabilitymentioning
confidence: 99%
“…The lack of such studies in the Amazon basin is due to the scarcity and heterogeneity of weather stations, especially regarding data access and the high number of failures (Ronchail et al, 2002;Debortoli et al, 2015;Santos et al, 2019). Data estimated by the Global Land Data Assimilation System (GLDAS) enable studies on the spatiotemporal variation of meteorological variables, as this product was developed from advanced land surface modeling and data assimilation methods (Rodell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%